Characterization and functional properties of pectin derived from leaves, pulp and seeds of lady’s finger (Abelmoschus esculentus Moench) - Abd Rahman, Nur Farhana (2014)
In Malaysia, lady‘s finger also known as okra (Abelmoschus Esculentus Moench) can be easily available all year round with low maintenance cost. In order to overcome issues regarding contamination of pork-related gelatin substance in food products, the development of plant based gelling agent was encouraged as an alternative to replace animal gelatin. Based on previous studies, okra plant was indicated as one of the more promising crops which possess unique properties of a gelling agent. Therefore, this study aims to extract, characterize the physicochemical and functional properties of pectin derived from okra leaves, pulp (skin without seeds) and seeds. Pectin was extracted using a sequential extraction with the applications of hot buffer (HB), hot buffer with chelating agents (CH), diluted alkali (DA) and concentrated alkali (CA) soluble solids. The fractions obtained were compared to commercial pectin in terms of functional group identification using Fourier Transform Infrared Spectroscopy (FTIR), nutritional composition, monosaccharide composition, pH, melting point, viscosity, gel strength and functional properties. Optimization of concentration was performed to determine the optimal concentration for gel formation and subjected to melting point, viscosity and gel strength analysis. The highest pectin yield was extracted from seeds with all fractions yield of 86%, followed by the leaves (75%) and pulp (71%). CH extraction gave the highest yield (>40%) compared to HB and DA from okra leaves, pulp and seeds. Nutritional composition showed total dietary fibre was the highest in okra leaves (65.06 ±1. 59) which was significantly different (p < 0.05) from okra pulp and seeds. HB fraction of leaves, pulp and seeds had highly purified pectin due to high anhydro uronic acid content and degree of esterification. Gel formation was achieved when okra pectin was blended together with konjac glucomannan (KG) and stored 16 - 18hr at 4°C ± 1.0 (5.0% of okra pectin: 1.6% of KG). The presence of major functional groups of pectin lies at 1,300-800 cm-1 in most of the HB, CH and DA fractions of okra leaves, pulp and seeds. Gel formation was identified by analysing gel strength and viscosity which showed HB had lower gel strength ( < 15 Bloom grams) than CH fraction, meanwhile DA fraction exceeds 50 (g) which generally failed to form a gel. Galacturonic acid and rhamnose were identified in all fractions of okra leaves, pulp and seeds by using HPLC-RI. Water and oil holding capacities of HB fraction from okra pulp were higher compared to others, meanwhile DA fractions of okra leaves showed a higher emulsifying ability and better foaming properties than the commercial pectin. Conclusively, characterization and functional properties of HB, CH and DA fractions derived from okra leaves, pulp and seeds showed potential use of the plant as gelling agent.